Scavenging activity nano complex compounds of kelor (Moringa oleifera Lamk.) leaves and seeds - Rafida Azizah; Tintrim Rahayu; Ari Hayati; Gatra Ervi Jayanti (The East Java Biological Society, 2020)
Moringa oleifera Lamk. is a good source of natural antioxidants because it contains various types of antioxidant compounds such as ascorbic acid, flavonoids, phenolics, and carotenoids. Those antioxidant components forming complex structure have transitional metal as central compound, which have free radical scavenging activity. This study aims to determine the active compounds that act as scavenger in leaves and seeds of M. oleifera. The possible compound found in leaves-seeds is elaborated by in silico analysis, using Dr. Duke's Phytochemical and Ethnobotanical Databases, by mean Pass online, and HitPick software. The results of in silico analysis 3 compounds identified in the leaves that had a high antioxidant role, namely beta-carotene, kaempferol, quercetin, and 2 compounds in seeds that had a high antioxidant role, namely alpha-tocopherol, beta-carotene. The results of this study indicate that the antioxidant activity of the 3 treatments had differences effectiveness of antioxidants. All of these antioxidants has ability to bind transitional metal to form free radical scavenger.